2010
DOI: 10.1002/ejlt.201000402
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of sesame, rice bran and bene hull oils and their unsaponifiable matters

Abstract: Chemical composition of sesame (SEO), rice bran (RBO) and bene hull (BHO) oils was determined. During oven test, peroxide value on day 8 (PV 8 , meq/kg) and carbonyl value on day 6 (CV 6 , mmol/g) were considered as measures of resistance to the formation of primary and secondary oxidation products, respectively. The SEO and BHO showed statistically the same PV 8 (381.4 and 359.8, respectively) and CV 6 (25.2 and 25.8, respectively), and their stabilizing effect was significantly better than that of the RBO (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
2
19
0
6
Order By: Relevance
“…It appears in a wooden hard shell coated with dark green hull containing highly stable and antioxidative oil (Farhoosh et al 2009). Interestingly, the antioxidant activity of the oil (non-volatile) during frying of sunflower oil has been higher than those of sesame and rice bran oils (Farhoosh et al 2011b). Local people use the fruits of Bene after grinding and mixing with other ingredients as foods, and unripe Bene are also used as jam.…”
Section: Introductionmentioning
confidence: 99%
“…It appears in a wooden hard shell coated with dark green hull containing highly stable and antioxidative oil (Farhoosh et al 2009). Interestingly, the antioxidant activity of the oil (non-volatile) during frying of sunflower oil has been higher than those of sesame and rice bran oils (Farhoosh et al 2011b). Local people use the fruits of Bene after grinding and mixing with other ingredients as foods, and unripe Bene are also used as jam.…”
Section: Introductionmentioning
confidence: 99%
“…Methanolic sesame extract was shown to possess major lignans like sesamolin and sesamin (Sukumar et al, ) and minor lignans such as acuminatolide, piperitol, and pinoresinol (Kuo et al, ). Methanolic extract was also reported to possess rich antioxidant activity than n ‐hexane extract which was corroborated to high lignans content (Farhoosh and Sharif, ). Further, lignans were reported for neuroprotective effects (Park et al, ) Hence, we decided to use methanol as solvent to prepare the extract of sesame seeds.…”
Section: Methodsmentioning
confidence: 86%
“…Farhoosh et al . () used toluene as the DPPH solvent and determined antioxidant capacities of vegetable oils, methanolic and hexane oil extracts, and unsaponifiable oil matter. Uluata & Ozdemir () tested the antioxidant activity of unconventional oilseeds, including stinging nettle, laurel, terebinth, hemp and radish, using DPPH in ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Prevc et al (2013) suggested that ethyl acetate could be an appropriate solvent for DPPH with refined oils, which have practically no polyphenols, while buffered alcohols are good for unrefined oils including extra virgin olive oil, sesame oil and pumpkin seed oil. Farhoosh et al (2013) used toluene as the DPPH solvent and determined antioxidant capacities of vegetable oils, methanolic and hexane oil extracts, and unsaponifiable oil matter. Uluata & Ozdemir (2012) tested the antioxidant activity of unconventional oilseeds, including stinging nettle, laurel, terebinth, hemp and radish, using DPPH in ethyl acetate.…”
Section: Changes Of Conventional Oxidation Parametersmentioning
confidence: 99%